IMPLEMENTATION STRATEGY OF SUSTAINABILITY AND HIGHEST BEST USE (SHBU) APPROACH FOR FELDA LAND DEVELOPMENT - Abdullah Kamar, Muhamad Asri; Mokhtar, Salbiah; Abdul Rashid, Mohd Fadzil; Kamaruddin, Siti Mazwin; Abdullah, Suzanah (PLANNING MALAYSIA, 2024)
Sustainability and Highest Best Use (SHBU) approach is believed to be useful in assisting the Federal Land Development Authority (FELDA) to develop its land towards improving settlers’ prosperity and livelihood. This research aims to demonstrate a proposed strategy for implementing the SHBU using a mixed methods approach which integrates interviews and Geographical Information System-based Multiple-criteria Decision Analysis (GIS-based MCDA). The interview component seeks to obtain feedback and development aspirations from respondents in FELDA Gunung Besout 03, while GIS technology generates and displays the findings in spatial forms to empower decision-making. Data were analysed using content analysis and spatial analysis accordingly. The findings from interview shows that generally, the SHBU approach is suitable for land development. Besides, GIS-based MCDA reveals four types of future land development spanning about 796 hectares encompassing cropland, residential areas, and small business centres. The findings become the basis for crafting the implementation strategies aimed at developing FELDA land within the study area.